2019
DOI: 10.1038/s41398-019-0457-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent behavioral deficits and neuropathology in a maternal immune activation model of autism

Abstract: Infections during gestation and the consequent maternal immune activation (MIA) increase the risk of developing neuropsychiatric disorders in infants and throughout life, including autism spectrum disorders (ASD). ASD is a neurodevelopmental disorder that affects three times more males than females and is mainly characterized by deficits in social communication and restricted interests. Consistent findings also indicate that ASD patients suffer from movement disorders, although these symptoms are not yet consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 59 publications
13
85
0
Order By: Relevance
“…While previous studies have shown that maternal immune conditions are more prevalent in mothers of children with ASD [23][24][25] , our results suggest that this may be influenced by offspring sex, a finding not described previously. These results are consistent with animal research suggesting that males are more vulnerable to more neurodevelopmental abnormalities after MIA [48][49][50][51][52] . Maternal immune conditions and maternal asthma were associated with increased CBCL scores and more impairment in children, particularly on the Externalizing and Total scales.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While previous studies have shown that maternal immune conditions are more prevalent in mothers of children with ASD [23][24][25] , our results suggest that this may be influenced by offspring sex, a finding not described previously. These results are consistent with animal research suggesting that males are more vulnerable to more neurodevelopmental abnormalities after MIA [48][49][50][51][52] . Maternal immune conditions and maternal asthma were associated with increased CBCL scores and more impairment in children, particularly on the Externalizing and Total scales.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, offspring sex may contribute to the differential outcomes observed between male and female children in the maternal immune and maternal non-immune groups. Increasing evidence from preclinical models suggests that male offspring are more susceptible to adverse outcomes as a result of MIA compared to female offspring [48][49][50][51][52] . Although these models typically rely on short-term exposures to infections rather than potentially ongoing or episodic activation from chronic maternal immune conditions, the preclinical observations support findings seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study identified sex-dependent molecular patterns that are consistent with the differential prevalence and symptoms of ASD, SSD, and MIA-related disorders between sexes reported in rodent and human studies (Wischhof et al, 2015). For example ASD tends to be more prevalent in young males (Kirsten et al, 2010;Haida et al, 2019), while SSD tends to be more prevalent in females (Bale et al, 2010;Bale, 2011). Similarly, lower sociability and preference for social novelty were observed in 2 weeks old pigs from gilts inoculated with PRRSV at GD 76 than from control gilts (Antonson et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…Thus, the prevalence of autism as well as characteristics of the autistic phenotypes are different in males vs. females [55][56][57][58] . Similarly, differences between males and females in the performance in ASD-associated behavioral tests were found in the Mthfr-deficient mice and in other autistic-like mouse models 18,[50][51][52]59,60 . Sex differences were also reported in the expression of several enzymes of the C1-metabolic pathway and in metabolite levels both regardless of the Mthfr genotype 23,61 and in Mthfr-deficient mice 23,62 .…”
Section: Discussionmentioning
confidence: 74%